Popular Movements and State Formation in Revolutionary Mexico : The Agraristas and Cristeros of Michoacan - Purnell, Jennie, 1957- (Book collections on Project MUSE., 1999)
Purnell reconsiders peasant partisanship in the cristiada of 1926-29, one episode in the broader Mexican Revolution.